Petrogenesis of high-CaO lavas from Mauna Kea, Hawaii: Constraints from trace element abundances. (15th July 2016) - Huang, Shichun; Humayun, Munir
Abstract: The role of a mafic component in the petrogenesis of Oceanic Island Basalts (OIBs) is highly debated. As the best studied OIB, Hawaiian lavas provide critical insights into OIB genesis. At a given MgO content, the CaO content in the melt has been used to distinguish between partial melts of peridotite and garnet pyroxenite/eclogite. However, calculations using the BATCH program show that CaO contents in volatile-free melts saturated with all four phases, garnet, clinopyroxene, orthopyroxene and olivine, are controlled by both degrees of partial melting and source compositions, and low melt CaO content is not diagnostic of partial melts from garnet pyroxenite/eclogite. This is an important consideration in understanding the origin of high-CaO lavas recovered from the Hawaii Scientific Drilling Project (HSDP). Detailed geochemical and isotopic studies have been focused on the HSDP high- and low-SiO2 group lavas, and high-CaO lavas were not well studied because they were not included in the original reference suite samples. Here, we report trace element abundances obtained on a suite of high-CaO glasses and compared the trace element abundances of high-CaO lavas to those in high- and low-SiO2 lavas. When normalized to the average composition of low-SiO2 lavas, high-CaO lavas form a U-shaped trace element pattern, enriched in both the most incompatible (Nb, Th) and the least incompatible (Sc, V) elements. This compositional distinction is best explained if high-CaO parental magma represents a mixture of a low degree partial melt of the low-SiO2 mantle source with a high degree (>80%) partial melt derived from a mafic cumulate component. This mafic cumulate must be clinopyroxene-rich, and it could be delaminated mafic cumulate formed under arcs during continent formation, lower continental crust, recycled lower oceanic crust, or high pressure cumulates from a magma chamber.